2008
DOI: 10.1016/j.ygyno.2008.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-dose rate gemcitabine plus docetaxel as second-line therapy for metastatic uterine leiomyosarcoma: A Gynecologic Oncology Group phase II study

Abstract: Objective-Doxorubicin-based treatment is standard therapy for metastatic uterine leiomyosarcoma. There is no standard second-line therapy. We determined activity of fixed-dose rate gemcitabine plus docetaxel as second-line treatment for metastatic uterine leiomyosarcoma.Methods-Eligible women with unresectable uterine leiomyosarcoma progressing after prior cytotoxic therapy were treated with gemcitabine 900 mg/m 2 days one and eight over 90 minutes, plus docetaxel 100 mg/m 2 on day 8 of a 21-day cycle with gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(144 citation statements)
references
References 32 publications
3
138
0
3
Order By: Relevance
“…A fixed-dose-rate infusion of gemcitabine at 10 mg/m 2 per minute may offer a pharmacologic advantage and has also been explored [25,28,29]. The activity of single-agent docetaxel has been reported to be quite limited, with response rates of 0%-18% [30 -32].…”
Section: Introductionmentioning
confidence: 99%
“…A fixed-dose-rate infusion of gemcitabine at 10 mg/m 2 per minute may offer a pharmacologic advantage and has also been explored [25,28,29]. The activity of single-agent docetaxel has been reported to be quite limited, with response rates of 0%-18% [30 -32].…”
Section: Introductionmentioning
confidence: 99%
“…The overall response rate and disease control rate were 20.0 and 60.0%, respectively. Hensley et al (16,17) investigated docetaxel (DOC) + GEM therapy in 42 patients with uterine LMS. The adverse events were grade ≥3 neutropenia in 17.0%, grade ≥3 anemia in 24.0% and grade ≥ thrombocytopenia in 14.5% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the objective response rate and median overall survival were also reported as 53 % and 17.9 months, respectively. In a another phase II study reported by Hensley et al (2008) the fixed-dose rate gemcitabine plus docetaxel was evaluated only as a second line therapy in patients with metastatic uterine leiomyosarcoma. In that study, the objective response rate and median OS were demonstrated as 27% (6.3% CR) and 14.7 months, respectively.…”
Section: Discussionmentioning
confidence: 99%